PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DI ARYADUTA HOTEL MANADO - Jelly Netty Sendow1; Rosilawati Karim (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2024)
This research aims to find out how service quality and price influence customer loyalty at Aryaduta Hotel Manado. The research method used in this research is the Quantitative Method, with Multiple Linear Regression data analysis techniques. The population in this research is hotel customers, with a sample of 30 customers at Aryaduta Hotel Manado. The results of this research prove that Service Quality and Facilities have a positive and significant effect on Customer Loyalty with a regression coefficient value of 17.844 and a significance of 0.003. This shows that the higher the Employee Service Quality, the higher the Customer Loyalty. Price has a significant positive effect on Customer Loyalty with a regression coefficient value of -2.854 and a significance of 0.000. This shows that the better the price offered at the hotel, the more customer loyalty will increase. Service Quality and Price have a significant influence on Customer Loyalty with a calculated F value of 238.073 and a significance of 0.000. This shows that the better the quality of service and price, the more customer loyalty will increase. The conclusion of this research is that service quality and price have a significant influence on customer loyalty at Aryaduta Hotel Manado. The advice given is that Aryaduta Hotel Manado must provide good service in accordance with applicable Standard Operating Procedures and provide prices offered according to what is promoted to increase customer loyalty visiting Aryaduta Hotel Manado.